On the Neumann Boundary Controllability for the Non-Homogeneous String on a Half-Axis - Khalina, K.S. (Журнал математической физики, анализа, геометрии, 2012)
In the paper, the equation of a vibrating non-homogeneous string, whose potential is not equal to a constant, is considered on a half-axis. The Neumann control of the class L∞ is considered at a point x = 0. The control problem is studied in the Sobolev spaces. The suffcient conditions for nullcontrollability and approximate null-controllability at a free time T > 0 are obtained for the given system. The controls solving these problems are found explicitly.